Expression of the AcrAB Components of the AcrAB-TolC Multidrug Efflux Pump of Yersinia enterocolitica Is Subject to Dual Regulation by OmpR - Raczkowska, Adrianna; Trzos, Joanna; Lewandowska, Olga; Nieckarz, Marta; Brzostek, Katarzyna (PloS one, 2015)
OmpR is a transcriptional regulator implicated in the control of various cellular processes and functions in Enterobacteriaceae. This study was undertaken to identify genes comprising the OmpR regulon in the human gastrointestinal pathogen Yersinia enterocolitica. Derivatives of an ompR-negative strain with random transposon insertions creating transcriptional fusions with the reporter gene lacZ were isolated. These were supplied with the wild-type ompR allele in trans and then screened for OmpR-dependent changes in β-galactosidase activity. Using this strategy, five insertions in genes/operons positively regulated by OmpR and two insertions in genes negatively regulated by this protein were identified. Genetic analysis of one of these fusion strains revealed that the gene acrR, encoding transcriptional repressor AcrR is negatively regulated by OmpR. Differential analysis of membrane proteins by SDS-PAGE followed by mass spectrometry identified the protein AcrB, a component of the AcrAB-TolC multidrug efflux pump, as being positively regulated by OmpR. Analysis of the activity of the acrR and acrAB promoters using gfp fusions confirmed their OmpR-dependent repression and activation, respectively. The identification of putative OmpR-binding sites and electrophoretic mobility shift assays confirmed that this regulator binds specifically to both promoter regions with different affinity. Examination of the activity of the acrR and acrAB promoters after the exposure of cells to different chemicals showed that bile salts can act as an OmpR-independent inducer. Taken together, our findings suggest that OmpR positively controls the expression of the AcrAB-TolC efflux pump involved in the adaptive response of Y. enterocolitica O:9 to different chemical stressors, thus conferring an advantage in particular ecological niches.